Occupational Safety Risk Analysis in Printing Area using JSA - Ningsih Dewi Sumaningrum; Mely Purnadianti (Jurnal Kesehatan dan Kedokteran, 2026)
Printing workplaces involve diverse operational activities that may pose occupational safety and health (OSH) risks to workers. Objective: This study aims to identify potential hazards and assess occupational risk levels in a printing facility using the Job Safety Analysis (JSA) method, considering that printing, cutting, ink handling, and manual material handling activities may lead to work-related injuries and health disorders. Methodology: A descriptive observational approach was employed. Data were collected through direct workplace observations, interviews with workers and supervisors, and a review of work process documentation. The JSA procedure involved breaking down work activities into sequential steps, identifying hazards at each stage, and determining risk levels along with appropriate control measures. Findings: The results revealed exposure to mechanical, chemical, physical, and ergonomic hazards. Mechanical hazards were predominantly associated with printing and cutting machine operations, posing risks of hand injuries and crushing incidents. Chemical hazards were identified during ink handling activities, with potential health effects from skin contact and inhalation exposure. Ergonomic hazards were mainly observed during manual material handling tasks, increasing the risk of musculoskeletal disorders. Several identified hazards were classified as medium to high risk, indicating the need for prioritized preventive actions. Implications: The findings highlight the importance of implementing integrated OSH control measures, including engineering controls, administrative actions, consistent use of personal protective equipment, and the strengthening of workplace safety culture to reduce occupational risks in printing environments. Originality: This study provides a systematic, task-based hazard mapping of core printing processes using JSA, offering practical guidance for prioritizing risk control strategies in printing operations with medium to high risk levels.